Pengukuran Kinerja Supply Chain Management Menggunakan Metode SCOR (Supply Chain Operation Reference), AHP (Analytical Hierarchy Process) dan OMAX (Objective Matrix) di PT. X - Inggitana Widya Kumala Putri; Dadang Surjasa (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
PT. X is a company that manufactures electronic equipment such as refrigerators, washing machines, televisions, and other products. This research was conducted only focusing on the refrigerator division. The refrigerator division has problems in the upstream supply chain. Therefore, companies need a measurement of the performance of Supply Chain Management (SCM). The purpose of this study is to measure the performance of SCM to find out indicators that are still far below the target and provide recommendations for improvement. SCM performance measurement is done by SCOR method for process decomposition, AHP for KPI hierarchy weighting, and OMAX for scoring system. The results of the research that have been analyzed with the Traffic Light System indicate that there are 9 KPIs from 22 valid KPIs that have never been in the green category. The total index results of the overall supply chain performance show that the lowest performance is in December 2017 with a total index of 3.5934 and the highest is in March 2018 with a total index of 7.002. There are 10 KPIs in the red and yellow categories in December which should be given more attention. Improvement recommendations are given to indicators that have never been in the green category. For example recommendations, DRS 2.3 KPI (supplier response speed in response to late arrival of raw materials at the factory) in improving its performance needs to do tracking of raw material shipments and additional shipping fleets or suppliers from suppliers.